Efficient cycloaddition of CO2 to epoxides using novel heterogeneous organocatalysts based on tetramethylguanidine-functionalized porous polyphenylenes. (May 2018) - Maya, Eva M.; Rangel-Rangel, Elizabeth; Díaz, Urbano; Iglesias, Marta
Graphical abstract: Highlights: Polyphenylene-Networks act as organic supports for functional sites as tetramethylguanidine (TMG). Polyphenylene-Networks display high surface areas and exhibit good CO2 adsorption properties. Porous polyphenylenes from tetraphenylbenzene, biphenyl and benzylamine have been prepared at gram-scale. TMG-polymers result excellent catalysts for the cycloaddition of CO2 to epoxides. TMG-polyphenylene-catalysts react under quite mild conditions without solvent. Abstract: The conversion of CO2 into cyclic carbonates by cycloaddition to epoxides is achieved under relatively mild reaction conditions (without solvent, 7 bar of CO2, 100 °C) using easily available heterogeneous tetramethylguanidine(TMG)-polyphenylene organocatalysts. These new highly stable catalysts were easily prepared by reaction of tetramethylurea in the presence of oxalyl chloride with aminomethyl polyphenylenes. The TMG-functionalized polyphenylene (2PhCH2 TMG) prepared from a pre-functionalized network was efficient and competitive compared with other reported catalysts achieving high epoxides conversion (>90%) and 100% selectivity towards the corresponding cyclic carbonates. The catalyst was easily separated from the reaction media and reused after basic regeneration without loss of activity.